Dismantling new democracies: the case of Tunisia. Issue 8 (17th November 2022) - Ridge, Hannah M.
ABSTRACT: After a decade as the stand-out democracy of the Middle East, Tunisia took an anti-democratic turn in July 2021 with President Kaïs Saïed's self-coup. Using a survey fielded in the weeks after these reforms, this article documents the substantial support for liberal institutions and civil rights in Tunisia. Democracy itself, on the other hand, is not so strongly supported. The study thus identifies potential for democratic backsliding in Tunisia through the strategic implementation liberal but anti-democratic actions. Other would-be authoritarians could follow Saïed's model of strategic regression to autocratize their regimes.